Analisis Crash Program pada Piutang Negara di Kantor Pelayanan Kekayaan Negara dan Lelang (KPKNL) Bandung Tahun 2021-2022 - Karima Fizana, Urba; Nurmalina, Rina (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
State receivables are part of state finances that need to be managed optimally in order to increase state revenues. One of the government's efforts to increase state revenues is through accelerating the settlement of state receivables by establishing a crash program. The purpose of this study is to analyze the crash program on state receivables at the KPKNL Bandung. The research method used is qualitative, with primary and secondary data obtained from interviews and documentation. Settlement of state receivables after the crash program mechanism was carried out at the KPKNL Bandung showed quite good results with the achievement of accelerated settlement of state receivables as indicated by an increase in the number of state receivables files that were completed with repayment and at the same time easing the debt burden of the debtor.